Trem2 regulates microglial migratory responses via type I interferon signaling during photoreceptor degeneration - Jincan He; Wenchuan Zhou; Jing Li (Cell Communication and Signaling)
Abstract Background Various functions of activated microglia play crucial roles in the progression of retinitis pigmentosa (RP). This study aims to investigate the mechanisms underlying microglial migratory responses and phagocytic activity and their effects on photoreceptor degeneration. Methods Trem2-deficient rd10 mice (Trem2 −/− :rd10) were used in this study. N-methyl-N-nitrosourea (MNU)-induced retinal degeneration was established in microglia-specific Trem2 overexpression mice (Tmem119 CreERT2 :Rosa26 CAG − LSL−Trem2 ). IFN-α/β receptor I (IFNAR1) neutralizing antibody was used to achieve type I interferon (IFN-I) signaling blockade. Terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL), immunofluorescent staining and western blot analysis were used to assess microglial responses and photoreceptor cell apoptosis. Microglia were purified with CD11b MicroBeads. Transcriptomic profiles of the whole retina were generated and analyzed. Results Progressive photoreceptor cell death and sustained microglial migratory responses were observed throughout the degeneration process in rd10 mice and MNU model. Trem2-deficient microglia displayed impaired migratory responses and subsequent phagocytosis, affecting photoreceptor cell survival at different stages of rd10 mice. Conversely, microglia-specific Trem2 overexpression mice showed enhanced microglial migration following MNU treatment. Furthermore, we found IFN-I signaling pathway was associated with microglial migration, which was regulated by TREM2 expression. Exogenous IFN-I blockade weakened microglial migration and reversed the effects of photoreceptor cell death caused by Trem2 overexpression. Conclusions Our findings demonstrated the divergent roles of Trem2-mediated microglial migratory responses and phagocytic activity at different stages of RP-featured retinal degeneration models. We identified the link between Trem2 and IFN-I signaling in microglia and provided a potential microglia-associated target for RP therapy.